HLA-B*15:01-positive severe COVID-19 patients lack CD8 + T cell pools with highly expanded public clonotypes - Louise C. Rowntree; Lilith F. Allen; Ruth R. Hagen; Hayley A. McQuilten; Ahmed A. Quadeer; Priyanka Chaurasia; Prathanporn Kaewpreedee; Kelly W. K. Lee; Carolyn A. Cohen; Jan Petersen; Dene R. Littler; Jennifer R. Habel; et al. (Proceedings of the National Academy of Sciences, 2025)
Understanding host factors driving asymptomatic versus severe disease outcomes is of key importance if we are to control emerging and re-emerging viral infections. HLA-B*15:01 has been associated with asymptomatic SARS-CoV-2 infection in nonhospitalized individuals of European ancestry, with protective immunity attributed to preexisting cross-reactive CD8 + T-cells directed against HLA-B*15:01-restricted Spike-derived S 919-927 peptide (B15/S 919 + CD8 + T-cells). However, fundamental questions remained on the abundance and clonotypic nature of CD8 + T-cell responses in HLA-B*15:01-positive patients who succumbed to life-threatening COVID-19. Here, we analyzed B15/S 919 + CD8 + T-cell responses in COVID-19 patients from independent HLA-typed COVID-19 patient cohorts across three continents, Australia, Asia and Europe. We assessed B15/S 919 + CD8 + T-cells in COVID-19 patients across disease outcomes ranging from asymptomatic to hospitalized critical illness. We found that severe/critical COVID-19 patients mounted B15/S 919 + CD8 + T-cell responses lacking a highly expanded key public B15/S 919 + CD8 + T-cell receptor (TCR; TRAV9-2/TRBV7-2) which recurred across multiple individuals in COVID-19 patients with a mild disease. Instead, B15/S 919 + CD8 + T-cell responses in life-threatening disease had a prevalence of an alternate TCR clonotypic motif (TRAV38-2/DV8/TRBV20-1), potentially contributing, at least in part, to why B15/S 919 + CD8 + T-cells in severe COVID-19 patients were less protective. Interestingly, the frequency, memory phenotype, and activation profiles of circulating B15/S 919 + CD8 + T-cells did not differ across disease severity. Moreover, B15/S 919 + CD8 + T-cells were better maintained into convalescence compared to other SARS-CoV-2-specificities. Our study thus provides evidence on the differential nature of the TCR clonal repertoire in 22.37% of HLA-B*15:01-positive COVID-19 patients who developed severe or critical disease in our cohorts, comparing to HLA-B*15:01-expressing individuals with mild COVID-19.